Industrialization of Medicine and Medical Professionalism: Bioethical Critiques - Joseph Tham, LC, Paul Lee & (Studia Bioethica, 2014)
Health care delivery system has changed into large multi-specialty groups or for-profit organizations primarily operated by financially oriented professional manager. These erosive for-profit tendencies within the medical profession have weakened trust relationship between physician and patient. The virtues and character of trust and justice of the physician and coordinated efforts among physicians, patients and society as a whole can strengthen the traditional trust relationship and can fulfill medical professionalism in the industrialized medical society.